The Polychaet [sic] fauna of South Africa. Part 5. Errant species dredged off Cape coasts - Day, J. H. (Annals of the South African Museum, 1960)
From introduction: "… earlier workers recorded 74 species of errant polychaets from below tide-marks. The present paper contains new records, notes or full descriptions of 171 species. 61 of them are species known from the earlier dredgings, 42 are species previously known only from the shore, 34 species are new records for South Africa, 22 are new species and 12 are doubtful species or new varieties."
World Polychaeta Database (WPolyD). Biostor has extracted pdf: http://biostor.org/reference/111532